Opportunities for Women as Guardians of Marriage in Indonesia: an Overview in the Sociology of Islamic Law - Islamy, Athoillah (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2020)
Whether we realize it or not, gender inequality is one of the social problems that we can easily find in people's lives. The problem of gender bias can occur in various aspects of life, including the aspect of legal rights, such as the right as guardian of marriage in Indonesia. This study aims to find a discourse analysis of the opportunities for women as marriage guardians in Indonesia. This study employs empirical normative legal method. The primary data sources are the Compilation of Islamic Law (KHI) and social observation. The secondary data sources used were various other relevant studies. Meanwhile, the theory used as a tool of analysis is the sociological theory of Islamic law from Ibn Qayyim al-Jauzi regarding changes in Islamic law. This study concludes that based on the pattern of equality of gender relations in Indonesian society, granting the right of authority as guardian of marriage to female relatives is a form of istihsan bi al-'urf, the change of law from general law (kulii) to special or casuistic law (juz'i) based on existing culture or custom. This is parallel with Ibn Qayyim's theory of change in Islamic law which makes conditions (ahwal) and culture ('adat) part of the factors of changing Islamic law.